Description of three new species related to Themus (Haplothemus) coriaceipennis (Fairmaire, 1889) (Coleoptera: Cantharidae) - Su, Junyan; Yang, Yuxia; Yang, Xingke (Zootaxa, 2015)
The male of Themus (Haplothemus) coriaceipennis (Fairmaire, 1889) is discovered and described for the first time. Three new species related to this species are described from China: T. (H.) rectus sp. nov., T. (H.) bimaculaticollis sp. nov. and T. (H.) licentimimus sp. nov., which are provided with the illustrations of habitus and genitalia of both sexes and abdominal sternites VIII of female. A key to the species related to T. (H.) coriaceipennis is also provided.